On the non-linearity of the willingness to commute - Börje Johansson; Johan Klaesson; Michael Olsson (European Regional Science Association (ERSA), 2002)
Established analysis of labour market commuting are based on random choice models and gravity type models. In these models generalised transport costs are formulated as exponential or loglinear distance-dependent functions. This paper presents empirical observations that imply that time-distances influence the commuting behaviour in a non-linear way, such that the time sensitivity is much lower for very short and long distances, whereas intermediate distance display a high time sensitivity. This is explained in a model which is parametrised and estimated. The results are important for understanding and predicting commuter behaviour. It also helps to delineate space, as in classical traditions, into local, intra-regional, and extra-regional space.
Keywords: 330